Strategi Guru dalam Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila Kelas IV di SD Negeri 5 Penatih - Ni Luh Meisa Pratiwi; Ni Nyoman Perni; Jayanthi Riva Prathiwi (Lembaga Pengembangan Kinerja Dosen, 2025)
Pancasila Education is a compulsory subject taught at every level of education, from elementary to higher education, with the aim of shaping students’ attitudes and behaviors based on the values of Pancasila in their daily lives. This study aims to describe the teacher's strategies in implementing the Problem Based Learning (PBL) model to enhance students' critical thinking skills in the Pancasila Education subject for fourth-grade students at SD Negeri 5 Penatih. The research focuses on three main aspects: (1) the implementation of PBL by teachers in improving students’ critical thinking in the topic